Reasons of shunt revision surgery for hydrocephalus - Šustickas, Gytis; Rimšienė, Justė (Lietuvos chirurgija, 2015)
Objectives To ascertain the rate of shunt revision and reasons for shunt revision surgery in patients with hydrocephalus. To evaluate the dependencies of hydrocephalus etiology, cerebrospinal fluid pressure before initial shunt surgery and implanted valve type with shunt revision and valve dysfunction rates. Materials and methods Retrospectively analysed operative reports and discharge summaries of 130 patients with hydrocephalus who underwent ventriculoperitoneostomy (VPS) surgery at the Department of Neurosurgery at the Vilnius University National Hospital during the period from 2007 to 2014. Information on each patient included age at initial shunt surgery, sex, etiology of hydrocephalus, the pressure of cerebrospinal fluid before the initial shunt surgery, site of ventricular catheter, patient’s condition estimated by Glasgow coma scale (GCS) before initial surgery, valve type, set valve opening pressure at implantation, rate of initial shunt surgeries, shunt revision rate, reasons for shunt revision. We compared shunt revision rate and valve dysfunction rate in patients with different etiology of hydrocephalus, different valve types implanted, different pressure of cerebrospinal fluid before surgery to find statistically significant correlations. To compare groups by shunt failure rate SPSS 22.0 program was used. Results Of the 130 treated patients, 49% were male, 51% were female. The average age of the patients was 55 ± 15,00 (range, 20–83). During the seven years period, 214 VPS surgeries were performed. For 64.6% of patients shunt surgery VPS was performed once, while 35.4% of patients required shunt revision. Reasons ascertained for shunt revision: obstruction of ventricular catheter – 2.17%, valve malfunction – 30.43%, obstruction of distal catheter – 10.87%, mixed shunt system block – 23.92%, shunt migration – 10.87%, shunt infection – 19.57%, exact rea son was not ascertained – 2.17%. Valve malfunction was identified as the most common reason for shunt revision. We compared valve dysfunction and shunt revision rates for patients with implanted valves from different manufacturers but no significant difference between them was determined. Shunt revision rate was not significantly different for patients with ventricular catheter tip in the frontal or occipital horn of lateral ventricles. Young age at initial shunt surgery (patients of 55 years or younger) was associated with a higher risk of shunt revision (p=0.047). Low pressure cerebrospinal fluid estimated before surgery was associated with higher risk of shunt revision compared with medium (p=0.035) and high pressure (p=0.036) cerebrospinal fluid. We confirmed significant reverse correlation that in the case of stenosis of cerebrospinal fluid pathways valve malfunction rate is lower in comparison to the other etiologies of hydrocephalus (p=0.012). Conclusions 35.4% of patients required shunt revision. Valve malfunction was identified as the most common reason for shunt revision. Patient’s age at the initial surgery as well as the etiology of hydrocephalus, and pressure of cerebrospinal fluid estimated before the initial surgery were significantly associated with shunt revision rate. Valve type, company and site of ventricular catheter in the frontal or occipital horn of lateral ventricles were not significantly associated with shunt revision rate.